Article Commentary: Pharmacokinetic and Pharmacodynamic of the Cognitive Enhancer Modafinil: Relevant Clinical and Forensic Aspects. Issue 2 (April 2020) - Sousa, Ana; Dinis-Oliveira, Ricardo Jorge
Modafinil is a nonamphetamine nootropic drug with an increasingly therapeutic interest due to its different sites of action and behavioral effects in comparison to cocaine or amphetamine. A review of modafinil (and of its prodrug adrafinil and its R -enantiomer armodafinil) chemical, pharmacokinetic, pharmacodynamic, toxicological, clinical and forensic aspects was performed, aiming to better understand possible health problems associated to its unconscious and unruled use. Modafinil is a racemate metabolized mainly in the liver into its inactive acid and sulfone metabolites, which undergo primarily renal excretion. Although not fully clarified, major effects seem to be associated to inhibition of dopamine reuptake and modulation of several other neurochemical pathways, namely noradrenergic, serotoninergic, orexinergic, histaminergic, glutamatergic and GABAergic. Due its wake-promoting effects, modafinil is used for the treatment of daily sleepiness associated to narcolepsy, obstructive sleep apnea and shift work sleep disorder. Its psychotropic and cognitive effects are also attractive in several other pathologies and conditions that affect sleep structure, induce fatigue and lethargy, and impair cognitive abilities. Additionally, in health subjects, including students, modafinil is being used off-label to overcome sleepiness, increase concentration and improve cognitive potential. The most common adverse effects associated to modafinil intake are headache, insomnia, anxiety, diarrhea, dry mouth and raise in blood pressure and heart rate. Infrequently, severe dermatologic effects in children, including maculopapular and morbilliform rash, erythema multiforme and Stevens-Johnson Syndrome have been reported. Intoxication and dependence associated to modafinil are uncommon. Further research on effects and health implications of modafinil and its analogs is steel needed to create evidence-based policies.